ADA HUBUNGAN ANTARA PEMBERIAN STIMULUS BAHASA DENGAN PERKEMBANGAN BAHASA BATITA - Nugroho, Yogi; Badi'ah, Atik; Sari K, Anastasia (MEDIA ILMU KESEHATAN, 2014)
Background: Children’s growth and development need to be stimulated by parents in order to be optimally achieved. Children with directed stimulation will develop faster than children with less or without stimulation. Language and verbal disorders are common problems in children with1.94% incidence in children under-five years old per year. Mothers tend to let the children’s language development flow naturally. Objectives: To investigate the correlation between language stimulation and language development of children under-tree-years oldin integrated care center Wirastri RW 14 Central Gamping, Sleman. Methods: Research was an analytical survey with cross sectional approach. Data were collected using questionnaires and DDST. Kendall’s tau test was used with significancy level of α <0.05. Results: Most of respondents applied language stimulation to their children (77.14%). The language development of children was mostly normal (68.6%). The p-value= 0.000 showed that there was a significant correlation between stimulation and language development, with a coefficient correlation of 0.597 that indicated a correlation in a medium strength. Conclusion: There was a correlation between language stimulation and language development in children under-tree-years old in integrated care center Wirastri RW 14 Central Gamping. Keywords: Children under-tree-years old, language development, language stimulation